Astragalus grahamianus extract: a novel source of bioactive compounds with antioxidant and neuroprotective activities - Khan, M.W.; Khan, R.A.; Ahmad, M.; Alkreathy, H.M.; Mushtaq, N.; Alam, O.; Khan, M.I.; Ullah, A.; Khan, H.U.; Haq, N.U.; Khan, W.R. (Instituto Internacional de Ecologia, 2024)
The Astragalus grahamianus (AG) Royle ex. Benth is traditionally used for the treatment of various human disorders. The current research work is aimed to explore the neuroprotective anti-Parkinson effects of various fractions of Astragalus grahamianus (A. grahamianus). Fine powder of Astragalus grahamianus was extracted with 70% methanol and then fractionated with various solvents on the basis of polarity. Standard protocols were used to investigate the bioactive constituents present in the various plant fractions. In-vitro antioxidant potential of various fractions was checked using diverse free radicals. In-vivo rats model was used to determined the neuroprotective effects of methanol fraction of A. grahamianus. The results revealed that various fractions of A. grahamianus contain flavonoids, cardiac glycosides, steroids, gums, terpenes, proteins, and carbohydrates except chloroform fraction lake the presence of steroids, cardiac glycosides, gums and saponins, aqueous fraction of steroids, terpenoids, gums and saponins, n-Hexane fraction steroids, carbohydrates, alkaloids, gums and flavonoids. The highest amount of total phenolic contents was found in AGME (32.67 ± 2.3 mg GAE/g). The AGME also showed enhanced free radicals cations potential against DPPH, ABTS and H2O2, respectively. The correlation between AOA (antioxidant activity) and TPC (total phenolic contents) revealed to be substantial. Relative R2 values for ABTS, H2O2, and DPPH activity are 0.9974, 0.9845, and 0.9678, respectively. The in-vivo neuroprotective activities showed significant results. Our findings highlight significant antioxidant, and neuroprotective possessions of AGME attributed to powerful bioactive compounds.